Ukrainian Identity in the Context of Memory and Forgetting: Philosophical and Anthropological Analysis - Khodzhaian, A. O.; Savchuk, N. V. (Anthropological Measurements of Philosophical Research, 2024)
Purpose. The main content of the presented study is a philosophical and anthropological analysis of the problem of memory in the context of the phenomenon of forgetting, the essential factors of establishing a new image of the Ukrainian person, his/her national memory and identity. This circumstance, in the situation of Ukraine’s defence against the Russian aggressor, upholding of freedoms and European values, poses the following tasks: 1) to undertake a consistent review of the conceptual content of the concepts of "memory" and "forgetting" and to identify their philosophical and anthropological content; 2) to analyse the phenomenon of national memory and show its significance for the struggle of the Ukrainian people for the European choice; 3) to study the main parameters of the process of forming a system of new values in the context of the phenomenon of forgetting in the discourse of philosophical anthropology. Theoretical basis. The complex and dynamic process of forming Ukrainian identity in the contexts of national memory and forgetting brings the system of life values to a new level of theoretical and methodological understanding. The philosophical and anthropological dimension of the values of a modern Ukrainian person allows us to engage the methodological discourses of memory studies, which are a way for people to construct their historical past in the perspective of creating a new future in the integrity of axiological, moral and existential content. The relevance of this problem is due to the crisis of worldview and cultural meanings of human existence in the context of war, the processes of which have a powerful impact on all aspects of social, political, and spiritual life, which ultimately leads to the need for a new type of communication, thinking, and behaviour. Originality. The study substantiates that the phenomenon of forgetting in the context of the formation of a new national memory largely determines the strategy of asserting Ukrainian identity in the context of modern civilizational challenges faced by Ukraine as a result of military aggression against its freedom and territorial integrity. This situation opens up new prospects for the formation of a civilizational system of values in interaction with a qualitatively different image of the Ukrainian person. Conclusions. Today, the Ukrainian state is facing an existential threat, which raises the problem of creating a new Ukrainian person whose worldview and system of values correspond to the image of a European person. Despite the serious problems that Ukraine has faced as a result of geopolitical contradictions on a global scale, philosophical and anthropological analysis has shown that the strategy of forming a new Ukrainian identity in the context of historical memory, which contains an element of forgetting, determines the process of creating a mentality that is consistent with the national strategy of entering Western civilisation. It is within the parameters of such an analysis that a new memory adequate to the needs of our time is formed.